The Contribution Of The Green Economy To Create Green Jobs In Algeria - Gouri, Assia (جامعة الوادي Univesity of Eloued, 2024)
This study Focuses on the role of the green economy in Algeria in creating green professions as a modern development approach based on linking the various development requirements, protecting the environment, and making more green professions that would alleviate poverty in many areas: Renewable energy Recycling waste and protecting biodiversity. The study concluded, through the results, that Algeria has achieved various projects and achievements in the framework of the green economy, but these results remain weak. From there, Algeria is required to reconsider the policies followed.
Keywords: green economy; green professions; renewable energy*